A permeabilidade da matriz agrícola influencia na estrutura da comunidade de médios e grandes mamíferos? - Pereira, Dara Maria Oliveira (2021)
The Atlantic Forest is mostly devastated. Being a highly endemic biome, the loss of his biodiversity is worrying. In the current century, the loss of species is much greater than the background and it is extremely important to understand how structural and seasonal factors of agricultural matrices influence the loss of biodiversity and biotic homogenization. This work aimed to test the hypothesis that agricultural matrices with simpler and more seasonal structures contribute to the homogenization of communities. To carry out the work, we used data from medium and large mammals (bady mass > 1 kg) from the Brazilian Atlantic Forest along with land use data and we performed the calculation of beta-diversity through mixed linear models, analyzing the best scale. Our results showed that structure is not a variable to consider and that more seasonal crops have more total beta diversity than less seasonal ones, which was contrary to our initial hypothesis. The hypothesis of biotic homogenization promoted by a greater seasonality of the matrices was rejected for the total beta diversity and corroborated for its turnover component.